ANALISIS GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA PADA BADAN PENDIDIDKAN DAN PELATIHAN (BADIKLAT) KOTA MAKASSAR - Adriani Adriani (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
In this study the methods used in data collection and field is literature , the type of data using qualitative and quantitative data with methods of descriptive analysis and regression analysis . The results of this study are the leaders in the education and training bodies tend to apply a style Makassar Democratic leadership , which leadership behaviors where the position of superior and subordinate is almost the same in the company but remains on the boundary . Employees are given the freedom , and leadership styles like this always think objectively . With the largest percentage is 59.69 % , in comparison with other leadership styles are Authoritarian 19.77 % and 20.53 % Leissez Fairez . The level of job satisfaction of employees in education and training bodies Makassar qualitatively at the level of